2009
DOI: 10.1159/000203331
|View full text |Cite
|
Sign up to set email alerts
|

Primary Renal Lymphoma: Report of Four Cases

Abstract: Background: Although secondary renal involvement from systemic lymphoma is very frequent, primary renal lymphoma is a rare entity. It is characterized by aggressive histopathology, very early extra-renal infiltration and poor prognosis. Case Reports: Here, we report 4 cases of primary renal lymphoma presenting with unilateral renal masses, which after radiological and clinical examination were assumed to be renal cell carcinoma. 3 patients were diagnosed with Non-Hodgkin’s lymphoma by nephrectomy and one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Otherwise, it has been briefly discussed in larger FNA series [5,7,8,9] or as small groups of case reports in the surgical pathology or oncology literature [10,11,12,13]. This series confirms that image-guided FNA is an accurate technique for diagnosing renal cell lymphoma, with only 2 nondiagnostic FNAs found in the series.…”
Section: Discussionmentioning
confidence: 55%
“…Otherwise, it has been briefly discussed in larger FNA series [5,7,8,9] or as small groups of case reports in the surgical pathology or oncology literature [10,11,12,13]. This series confirms that image-guided FNA is an accurate technique for diagnosing renal cell lymphoma, with only 2 nondiagnostic FNAs found in the series.…”
Section: Discussionmentioning
confidence: 55%
“…[8][9] Primary renal lymphoma typically presents in age above 40, with flank pain, weakness, weight loss, hematuria, abdominal mass or renal failure. [4][5] Kidney does not have lymphoid tissue, 10 but repetitive injury to renal lymphatics due to chronic inflammation may cause malignant transformation to neoplasia of the lymphoid tissue. This occurs in extra nodal MALT lymphoma, which affects the skin, the gastrointestinal tract and the breast.…”
Section: Discussionmentioning
confidence: 99%
“…12 Diagnosis is a challenge; it is sometimes difficult to distinguish MALT lymphomas from more common tumours, such as renal cell carcinoma (RCC), in imaging studies; diagnosis, however, can be confirmed with a CT-guided biopsy of the mass. 4 In most cases, diagnosis is made after radical nephrectomy for the suspected RCC. MALT lymphomas can be treated with chemotherapy, surgical intervention or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Medical records and literature mention several cases of malignant kidney lymphoma [1, 2]. Some authors claim that this entity accounts for 3% of all solid renal tumors among adults [3].…”
Section: Discussionmentioning
confidence: 99%